2015
DOI: 10.1111/medu.12727
|View full text |Cite
|
Sign up to set email alerts
|

Medical electives in sub-Saharan Africa: a host perspective

Abstract: The challenge to both students and their sending institutions is to progress towards giving something proportionate back in return for the learning experiences received. There is clearly room to improve electives from the hosts' perspective, but individually host institutions lack the opportunity or ability to achieve change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(151 citation statements)
references
References 17 publications
4
146
1
Order By: Relevance
“…Overall, respondents evaluated STEGH students’ capabilities as being those from the pre‐clerkship academic level and did not identify any current situations resulting in ethical incidents. This result differs from other studies that found potential ethical challenges: lack of sustainability of students’ actions, handling of White privilege, precariousness of resources and performance of procedures beyond the students’ skills . This difference could be due in part to the fact that, for the past 5 years, STEGH students in our study context have undergone mandatory pre‐departure training.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Overall, respondents evaluated STEGH students’ capabilities as being those from the pre‐clerkship academic level and did not identify any current situations resulting in ethical incidents. This result differs from other studies that found potential ethical challenges: lack of sustainability of students’ actions, handling of White privilege, precariousness of resources and performance of procedures beyond the students’ skills . This difference could be due in part to the fact that, for the past 5 years, STEGH students in our study context have undergone mandatory pre‐departure training.…”
Section: Discussioncontrasting
confidence: 85%
“…In sub‐Saharan Africa, various researchers have investigated the perceptions of medical school professionals and students regarding STEGH. One common finding was that visiting medical students and professionals often took advantage of their economic and political power to impose their conceptions of health care without making any effort to immerse themselves in and understand the host context . Respondents also thought that visiting students primarily wanted to take advantage of lax laws and regulations to gain medical knowledge .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some settings the educational experience may be compromised if students are exposed to health risks, including infectious disease, ethical dilemmas or other adverse events . Although institutions appear to value hosting students from other countries, concerns have been raised about resources, student behaviour, differences in expectations and inequitable exchange . Although this report is from the UK, the shared experiences of academics and support teams whose students leave the ‘home’ site to experience a health care context elsewhere means themes presented above have resonance internationally.…”
Section: Background and Rationalementioning
confidence: 99%
“…Advocating for reciprocity can partially mediate this concern [18,51], although bi-directional exchange requires additional resources, and, in many cases, travel opportunities are further complicated by inequalities in global visa systems. Without an orientation to local culture, language, and the plural healthcare practices of communities, it is difficult for GHCs to provide value [20,52]. An additional burden is often placed on local hosts to transport, house, feed, and translate for GHCs, thereby potentially sidelining their own areas of responsibility in favor of the interests and projects of visiting clinicians [53].…”
Section: Introductionmentioning
confidence: 99%